DEGRADASI SENYAWA 2,4 (DIKLOROFENOKSI) ASAM ASETAT DALAM PESTISIDA SIDAMIN 865 AS SECARA FOTOLISIS DENGAN PENAMBAHAN TiO2-ANATASE - Hakim, Abinul; -, Safni; Suyani, Hamzar; Sakai, Tadao (Jurnal Riset Kimia, 2009)
ABSTRACT Degradation of 2,4-Dichlorophenoxyacetic Acid (2,4-D) in Sidamin 865 AS pesticides had been carried out by photolysis with adding anatase-TiO2. Photolysis method were performed using an irradiation of UV-light at λ 365 nm, 10 W. The degradation of 20 mg/L 2,4-D without addition of anatase-TiO2 was 6.88% within 90 minutes treatment. Degradation of 20 mg/L 2,4-D by photolysis with addition of 0.1000 g anatase-TiO2, degradation was 31.55% within 90 minutes irradiation without stirring and it was 95.42% within 90 minutes irradiation with stirring. Keywords : photolysis, 2,4-dichlorophenoxyacetic acid, anatase-TiO2